Chemical-corrosion-resistant easy-to-clean organic silicon modified acrylic adhesive and preparation method thereof
By combining components such as methacryloyloxyacrylate monomer, acryloyloxyacrylate monomer, unsaturated organosilane and other components with specific ratios, the problem of adhesives being easily corroded and absorbed in agricultural drones is solved, and an adhesive with high chemical corrosion resistance and easy cleaning is achieved, which improves structural stability and service life.
Patent Information
- Application Number
- CN202411979439.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Existing silicone modified acrylic adhesives are susceptible to corrosion and adsorbing of dirt in agricultural drones, such as pesticides and other chemicals, resulting in difficulty in cleaning and affecting structural stability and service life.
The specific ratios of methacryloyloxyacrylate monomer, acryloyloxyacrylate monomer, unsaturated organosilane, branched hydroxyl polyester, nanofiller and reactive diluent are used to improve the chemical corrosion resistance and pollution resistance of the adhesive through combination and synergistic action.
It significantly improves the chemical corrosion resistance and pollution resistance of adhesives, reduces the corrosion and stain adhesion of pesticides and other chemicals, improves the difficulty of cleaning and structural stability, and extends the service life and safety of the product.
Smart Images

Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of adhesives, and more specifically, to a chemically resistant and easy-to-clean organosilicon-modified acrylic adhesive and a preparation method thereof. Background Art
[0002] With the advancement of science and technology, various electronic products have developed rapidly, especially in the fields of new energy vehicles and drones, and the requirements for materials are getting higher and higher. The applications in these fields require not only high-performance electronic equipment, but also reliable connection and fixing materials to ensure the safety and stability of the products. For example, in new energy power battery packs, the fixation, sealing, and potting of battery cells are key links; on drones, the connection and fixation of various components such as wings, tails, and fuselages are also essential. In addition, for the fixation and sealing of electronic components such as circuit boards, sensors, and batteries, efficient and stable adhesives are also needed to provide protection to prevent damage caused by vibration or impact.
[0003] In order to meet the above requirements, the existing technology mainly uses silicone modified acrylic adhesives. This type of adhesive combines the advantages of silicone and acrylic, and has excellent weather resistance, aging resistance, high bonding strength and good flexibility. It can improve the stable fixation and sealing of various structures in new energy batteries and drones, and improve their structural stability.
[0004] However, when silicone-modified acrylic adhesives are used for sealing and structural connections of agricultural drones, since agricultural drones are usually used for crop monitoring and pesticide application, especially pesticide application, during long-term use, pesticides and other chemicals can easily corrode the connection structure or sealing structure formed, and the adhesive surface can easily absorb dirt, making cleaning difficult. In the long run, this affects the stability of the structure, which not only affects the appearance of the product, but may also reduce its service life and safety.
[0005] Based on the above problems, the above problems are currently solved by introducing fluorine-containing reactive monomers, but fluorine-containing reactive monomers may produce fluoride pollution during production and use, and pose a potential threat to the environment and ecosystem. Therefore, how to develop an organic silicon-modified acrylic adhesive that is both environmentally friendly, chemically resistant and easy to clean has become a technical problem that needs to be solved urgently. Summary of the invention
[0006] In order to reduce pollution to the ecological environment and obtain a silicone-modified acrylic adhesive with better corrosion resistance and pollution resistance, especially corrosion resistance and pollution resistance to chemicals such as pesticides, the present application provides a chemically resistant and easy-to-clean silicone-modified acrylic adhesive and a preparation method thereof.
[0007] In a first aspect, the present application provides a chemically resistant and easy-to-clean silicone-modified acrylic adhesive, which is composed of the following raw materials in percentage by weight: Methacryloyloxy acrylate monomer: 38-60%; Acryloyloxy acrylate monomer: 5-20%; Unsaturated organosilane: 9-22%; Branched hydroxy polyester: 0.1-2%; Nanofiller: 1-5%; Initiator: 1-3%; The balance is active diluent; The methacryloyloxy acrylate monomer is 2-methacryloyloxyethyl phthalate and / or mono-2-(methacryloyloxy)ethyl maleate; The acryloxy acrylate monomer is one or more of 9,9-bis[4-(2-acryloxyethoxy)phenyl], ethoxylated bisphenol A diacrylate, and 2-phenoxyethyl acrylate.
[0008] By adopting the above technical solution, through the compounding and specific proportion of methacryloyloxy acrylate monomer and acryloxy acrylate monomer, the adhesive has excellent corrosion resistance and pollution resistance, especially pollution resistance and cleanliness for chemicals such as pesticides.
[0009] Branched hydroxy polyester has excellent adhesion and cohesion, while improving surface wettability, reducing stain adhesion and increasing the ease of cleaning. The synergistic effect of branched hydroxy polyester and acrylate monomers can give the material good chemical resistance, while methacryloyloxy acrylate monomers and acryloxy acrylate monomers can improve its chemical stability and adhesion. Therefore, after the three are compounded, the resistance of the silicone-modified acrylic adhesive to chemicals such as pesticides after curing can be further improved. Unsaturated organosilicon further reacts with methacryloyloxy acrylate monomers, acryloxy acrylate monomers, and branched hydroxy polyesters to introduce siloxanes, further enhancing chemical corrosion resistance and anti-pollution properties.
[0010] Nanofillers can fill tiny pores on the surface of materials, improving the surface finish and flatness. At the same time, the hydrophobicity of unsaturated organosilicon can reduce the affinity of the material surface with water, making the synergistic effect of nanofillers and unsaturated organosilicon more difficult for stains to adhere.
[0011] By adding active diluents, the viscosity of the silicone-modified acrylic adhesive can be reduced, making it easier to potting and coating. At the same time, the diluent can also promote uniform mixing between the components, improve the uniformity of the raw material system, and obtain better comprehensive performance after the silicone-modified acrylic adhesive is fully cured. In addition, this application uses solvent-free glue, and the formula does not contain fluorine and other substances, which can protect the environment to a greater extent.
[0012] In summary, the components of the present application, such as methacryloyloxy acrylate monomer, acryloxy acrylate monomer, unsaturated organosilane, branched hydroxy polyester, nanofiller, initiator and active diluent, cooperate with each other to play a synergistic role, further enhancing the easy cleaning and chemical corrosion resistance of the silicone-modified acrylic adhesive after being used for UAV structure connection or sealing, especially the corrosion resistance and anti-pollution against chemicals such as pesticides.
[0013] Preferably, the acryloxy acrylate monomer is composed of 9,9-bis[4-(2-acryloxyethoxy)phenyl], ethoxylated bisphenol A diacrylate, and 2-phenoxyethyl acrylate in a weight ratio of 1:(1.5-3):(2-5).
[0014] By adopting the above technical solution, the acryloxy acrylate monomer is compounded with 9,9-bis[4-(2-acryloyloxyethoxy)phenyl], ethoxylated bisphenol A diacrylate, and 2-phenoxyethyl acrylate in a specific weight ratio, so that the adhesive has excellent chemical corrosion resistance and anti-pollution properties. The various components in the combination work together to improve the overall performance of the adhesive, especially in resisting the erosion of pesticides and other chemicals and reducing the adhesion of stains.
[0015] Preferably, the methacryloyloxy acrylate monomer is composed of 2-methacryloyloxyethyl phthalate and mono-2-(methacryloyloxy)ethyl maleate in a weight ratio of 1:(0.5-1.5).
[0016] By adopting the above technical solution, the methacryloyloxy acrylate monomer is composed of 2-methacryloyloxyethyl phthalate and / or mono-2-(methacryloyloxy)ethyl maleate in a weight ratio of 1:(0.5-1.5), which can effectively improve the chemical corrosion resistance and anti-pollution properties of the adhesive. The compounding under this specific ratio makes the interaction between the two monomers more coordinated, thereby further improving the comprehensive performance of the adhesive on the basis of ensuring good adhesion, especially in terms of pesticide corrosion resistance and anti-pollution performance.
[0017] Preferably, the unsaturated organosilane is methacrylate mono-terminated dimethylpolysiloxane and / or acrylic-cage polysilsesquioxane.
[0018] By adopting the above technical solution, the addition of methacrylate mono-terminated dimethyl polysiloxane and / or acrylic-cage polysilsesquioxane significantly improves the chemical corrosion resistance and anti-pollution properties of the adhesive. The siloxane structure in these unsaturated organic silane molecules gives the adhesive excellent hydrophobicity and surface smoothness, reduces the adhesion of pollutants, and makes the adhesive surface easier to clean. At the same time, these siloxane compounds also enhance the cohesion and mechanical properties of the adhesive, so that it can still maintain good bonding strength and stability in harsh environments.
[0019] Preferably, the unsaturated organic silane is composed of methacrylate mono-terminated dimethyl polysiloxane and acrylic-cage polysilsesquioxane in a weight ratio of (2-3):1.
[0020] By adopting the above technical solution, methacrylate mono-terminated dimethylpolysiloxane and acrylic-cage polysilsesquioxane are compounded in a specific ratio, which significantly improves the chemical corrosion resistance and anti-pollution properties of the adhesive. Specifically, methacrylate mono-terminated dimethylpolysiloxane enhances the water resistance and weather resistance of the adhesive, while acrylic-cage polysilsesquioxane improves the mechanical properties and surface characteristics of the adhesive. The synergistic effect of the two enables the adhesive to maintain excellent stability and reliability in complex environments.
[0021] Preferably, the nanofiller is PI powder and / or silicone powder.
[0022] Among them, in terms of easy cleaning, PI powder and silicone powder have low surface energy characteristics and lubricity, making their adhesives smooth and not easy to be contaminated.
[0023] In terms of chemical corrosion resistance, PI powder and silicone powder both have corrosion resistance. When used as nanofillers in adhesives, they can form a protective layer that effectively blocks the penetration of corrosive substances. Therefore, the addition of the above nanofillers allows the adhesive to have better chemical corrosion resistance and easy cleaning properties while maintaining good bonding properties. The corrosion resistance of the adhesive is improved, especially in harsh environments such as pesticides and other chemicals, dust, etc. Therefore, the use of the nanofillers of this application, in combination with other raw materials of this application, can obtain better comprehensive performance.
[0024] Preferably, the nanofiller is composed of PI and silicone powder in a weight ratio of (1-3):1.
[0025] By adopting the above technical solution, the nanofiller is composed of PI and silicone powder in a weight ratio of 1: (1-3), which further improves the mechanical strength and pesticide corrosion resistance of the adhesive, improves the surface smoothness of the adhesive, makes it easier to clean, and reduces the corrosion and other phenomena that occur after being used in agricultural drones, thereby affecting the stability of the structure.
[0026] PI powder is polyimide powder, which is preferably Evonik UHT.
[0027] Preferably, the initiator consists of a photoinitiator and a thermal initiator.
[0028] By adopting the above technical solutions, the combined use of photoinitiators and thermal initiators can significantly improve the curing speed and efficiency of adhesives, while ensuring the applicability and stability of adhesives under different environmental conditions. Photoinitiators can quickly initiate polymerization reactions under light conditions and are suitable for application scenarios that require rapid curing; thermal initiators can continue to work in high temperature environments, ensuring that adhesives can still be effectively cured under complex working conditions, improving overall performance and reliability.
[0029] Preferably, the reactive diluent is epoxidized soybean oil.
[0030] By adopting the above technical solution, epoxidized soybean oil as an active diluent can effectively reduce the viscosity of the system, improve processing performance, and increase the curing speed and mechanical properties of the adhesive. These characteristics make the adhesive have better construction convenience and higher bonding strength in practical applications.
[0031] In a second aspect, the present application provides a method for preparing a chemically resistant and easy-to-clean silicone-modified acrylic adhesive, comprising the following steps: According to weight percentage, methacryloyloxy acrylate monomer, acryloxy acrylate monomer, unsaturated organosilane, branched hydroxy polyester, nanofiller, initiator and reactive diluent are weighed and mixed evenly to obtain an organosilicon-modified acrylic adhesive.
[0032] By adopting the above technical solution, the preparation method ensures that the components are accurately mixed in a specific ratio, thereby obtaining a silicone-modified acrylic adhesive with excellent chemical corrosion resistance and easy cleaning. When used in agricultural drones, it can reduce the phenomenon of pesticide corrosion, and the adhesive surface is not easily contaminated or adsorbed by pesticides, dust, etc., thereby improving the durability and easy cleaning of agricultural drones.
[0033] In summary, this application has the following beneficial effects: 1. The specific ratio of methacryloyloxy acrylate monomer and acryloxy acrylate monomer significantly improves the chemical corrosion resistance and anti-pollution ability of the adhesive, effectively solving the problem that the adhesive in the prior art is easily corroded by chemicals such as pesticides and adsorbs dirt.
[0034] 2. The introduction of branched hydroxyl polyester enhances the adhesion and cohesion of the adhesive, allowing the adhesive to form a strong bonding layer on the surface of a variety of materials. At the same time, it improves the surface wettability, reduces the adhesion of stains, and improves the convenience of cleaning.
[0035] 3. The addition of unsaturated organosilane further enhances the weather resistance and aging resistance of the adhesive, enabling it to maintain good performance in harsh environments and extending the service life and safety of the product. DETAILED DESCRIPTION
[0036] The present application is further described in detail below with reference to the embodiments.
[0037] Some raw materials: Branched hydroxy polyester Covestro 670; Methacrylate mono-terminated dimethylpolysiloxane CAS No. 146632-07-7; The PI powder and silicone powder used in this application are obtained by grinding, and the particle size is 100-500nm; the brand model of silicone powder is Yinyuan SR-402; Epoxidized soybean oil. Example
[0038] Example 1 The preparation of a chemical corrosion resistant and easy-to-clean organosilicon modified acrylic adhesive comprises the following steps: According to weight percentage, 38% of methacryloyloxy acrylate monomer, 20% of acryloyloxy acrylate monomer, 22% of unsaturated organosilane, 0.1% of branched hydroxy polyester, 1% of nanofiller, 3% of initiator, and 15.9% of active diluent were weighed and put into a stirring device, and stirred at a speed of 40 r / min for 10 minutes to fully mix them to obtain a silicone-modified acrylic adhesive.
[0039] The methacryloyloxy acrylate monomer is 2-methacryloyloxyethyl phthalate; the acryloyloxy acrylate monomer is 2-phenoxyethyl acrylate; the unsaturated organic silane is methacrylate mono-terminated dimethyl polysiloxane; the nanofiller is PI powder, and the initiator is composed of photoinitiator 1301 and thermal initiator BPO in a weight ratio of 1:3. The active diluent is epoxidized soybean oil.
[0040] Example 2-3 The difference between Example 2-3 and Example 1 is that the amount of raw materials used is different, as shown in Table 1; Table 1 Raw material dosage of Examples 1-3 (%) Example 4 The difference between Example 4 and Example 1 is that the methacryloyloxy acrylate monomer is mono-2-(methacryloyloxy)ethyl maleate.
[0041] Example 5 The difference between Example 5 and Example 2 is that the methacryloyloxy acrylate monomer is composed of mono-2-(methacryloyloxy)ethyl maleate and 2-methacryloyloxyethyl phthalate in a weight ratio of 1:1.5.
[0042] Example 6 The difference between Example 6 and Example 2 is that the methacryloyloxy acrylate monomer is composed of mono-2-(methacryloyloxy)ethyl maleate and 2-methacryloyloxyethyl phthalate in a weight ratio of 1:0.5.
[0043] Example 7 The difference between Example 7 and Example 2 is that the acryloxy acrylate monomer is 9,9-bis[4-(2-acryloxyethoxy)phenyl].
[0044] Example 8 The difference between Example 8 and Example 2 is that the acryloxy acrylate monomer is ethoxylated bisphenol A diacrylate.
[0045] Example 9 The difference between Example 9 and Example 2 is that the acryloxy acrylate monomer is composed of 9,9-bis[4-(2-acryloxyethoxy)phenyl], ethoxylated bisphenol A diacrylate, and 2-phenoxyethyl acrylate in a weight ratio of 1:1:2.
[0046] Example 10 The difference between Example 10 and Example 5 is that the acryloxy acrylate monomer is composed of 9,9-bis[4-(2-acryloxyethoxy)phenyl], ethoxylated bisphenol A diacrylate, and 2-phenoxyethyl acrylate in a weight ratio of 1:1:2.
[0047] Embodiment 11 The difference between Example 11 and Example 2 is that the unsaturated organosilane is an acrylic-cage polysilsesquioxane.
[0048] Example 12 The difference between Example 12 and Example 2 is that the unsaturated organosilane is composed of methacrylate mono-terminated dimethylpolysiloxane and acrylic-cage polysilsesquioxane in a weight ratio of 2:1.
[0049] Embodiment 13 The difference between Example 13 and Example 10 is that the unsaturated organosilane is composed of methacrylate mono-terminated dimethyl polysiloxane and acrylic-cage polysilsesquioxane in a weight ratio of 2:1.
[0050] Embodiment 14 The difference between Example 14 and Example 2 is that the nanofiller is PI powder.
[0051] Embodiment 15 The difference between Example 15 and Example 2 is that the nanofiller is silicone powder.
[0052] Example 16 The difference between Example 16 and Example 2 is that the nanofiller is composed of PI powder and silicone powder in a weight ratio of 2:1.
[0053] Embodiment 17 The difference between Example 17 and Example 13 is that the nanofiller is composed of PI powder and silicone powder in a weight ratio of 3:1.
[0054] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that the methacryloyloxy acrylate monomer is replaced by an acryloxy acrylate monomer in equal amounts.
[0055] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that an equal amount of acryloxy acrylate monomer is replaced by a methacryloxy acrylate monomer.
[0056] Comparative Example 3 The difference between Comparative Example 3 and Example 2 is that the branched hydroxy polyester is replaced by an equal amount of unsaturated organosilane.
[0057] Comparative Example 4 The difference between Comparative Example 4 and Example 2 is that the acrylate monomer B is replaced by acrylic acid amide.
[0058] Comparative Example 5 The difference between Comparative Example 5 and Example 2 is that the unsaturated organic silane is replaced by silane coupling agent 550.
[0059] Comparative Example 6 The difference between Comparative Example 6 and Example 2 is that the amount of methacryloyloxy acrylate monomer used is exchanged with the amount of acryloxy acryloyloxy acrylate monomer used.
[0060] Performance testing 1) The organosilicon-modified acrylic adhesive obtained in Examples 1-17 and Comparative Examples 1-6 was applied to the surface of an aluminum alloy plate, cured at 60° C. for 10 min, and then UV-cured for 1 min. After standing for 24 h, a coating with a thickness of 1 mm was formed on the surface to obtain a test sample.
[0061] 2) The organosilicon-modified acrylic adhesive obtained in Examples 1-17 and Comparative Examples 1-6 was used to bond a carbon fiber sheet and an aluminum alloy sheet, and cured at 60°C for 10 min, and then UV cured for 1 min. After standing for 24 h, a shear strength test specimen for the following test standard was obtained, wherein the surfaces of the carbon fiber sheet and the aluminum alloy sheet were both flat.
[0062] Detection method / test method Spraying experiment: Place the test sample in 1) and the test sample in 2) in the spray test device at 45°, and spray the pesticide on the test sample and the test sample through the spray device. The spraying conditions of the spray test device are that the spray aperture is 10mm, and the entire test sample and the test sample are fully covered, the pesticide flow rate is 100L / min, and the spray pressure is 220kPa; and the spray device is equipped with a UV lamp inside, and the UV lamp irradiates the entire sample, the wavelength of the UV lamp is 320nm, and the internal temperature is maintained at 35℃, and the test is continuously tested for 7 days. After the test is completed, take out the sprayed test sample and test sample, and then rinse them with clean water. The rinse process is fully covered, and the water flow rate is 200L / min, the spray pressure is 250kPa, and the rinse time is 5min. Then enter the oven for drying for 2h, and the drying temperature is 50℃ to obtain the test sample and test sample after spraying.
[0063] The pesticide consists of glyphosate, acetochlor, water and nano silicon dioxide in a weight ratio of 1:1:10:0.1.
[0064] Test 1: Tensile shear strength. Refer to the method specified in GB / T 7124-2008 to obtain the test specimens before and after spraying. Record the corresponding experimental data after the test, and the shear strength residual rate is equal to the shear strength of the test specimen after spraying divided by the shear strength of the test specimen before spraying, multiplied by 100%.
[0065] Test 2: Refer to GB / T 30693-2014 to detect the contact angle. Test the test sample before and after spraying. Drop water on the coating and record the relevant experimental structure. The change rate of the water drop angle is equal to 1-(the contact angle of the test sample before spraying minus the contact angle of the test sample after spraying, divided by the contact angle of the test sample before spraying)*100%.
[0066] The above experimental data are shown in Table 2. Table 2 Experimental data of Examples 1-17 and Comparative Examples 1-6 Combining Example 1 and Comparative Examples 1-6 and Table 2, it can be seen that the shear strength and shear strength residual rate of Comparative Examples 1-6 are greater than the shear strength and shear strength residual rate of Example 1, indicating that the glue on the test sample of Example 1 has better corrosion resistance and adhesion stability, and the water drop angle change rate of Comparative Examples 1-6 is greater than the water drop angle change rate in Example 1, indicating that the glue layer on the test sample is not easy to be stained or adsorbed with stains, further indicating that the curing of the silicone modified acrylic adhesive in Example 1 has better easy cleaning. It further indicates that the raw material composition and dosage of the present application can cooperate with each other to further improve the pesticide corrosion resistance and easy cleaning of the silicone modified acrylic adhesive after curing, and improve the service life and safety of the drone.
[0067] Compared with Example 2, the shear strength and shear strength residual rate of Examples 5, 9, and 12 are greater than those of Example 2, and the water drop angle change rate of Examples 5, 9, 12, and 16 is smaller than that of Example 2, indicating that the present application is compounded by maleic acid mono-2-(methacryloyloxy)ethyl ester and 2-methacryloyloxyethyl phthalate; or 9,9-bis[4-(2-acryloyloxyethoxy)phenyl], ethoxylated bisphenol A diacrylate, and 2-phenoxyethyl acrylate; or methacrylate mono-terminated dimethylpolysiloxane and acrylic-cage polysilsesquioxane; or PI powder and silicone powder, all of which play a synergistic role to further improve pesticide corrosion resistance and easy cleaning.
[0068] It is only an explanation of the present application and not a limitation of the present application. After reading this specification, a person skilled in the art can make non-creative modifications to the present embodiment as needed, but as long as it is within the scope of the claims of the present application, it is protected by the patent law.
Claims
1. A chemical corrosion resistant and easy-to-clean organosilicon modified acrylic adhesive, characterized in that: It is composed of the following raw materials in weight percentage: Methacryloyloxy acrylate monomer: 38-60% Acryloyloxy acrylate monomer: 5-20% Unsaturated organosilane: 9-22% Branched hydroxy polyester: 0.1-2% Nano filler: 1-5% Initiator: 1-3% The balance is active diluent; The methacryloyloxy acrylate monomer is 2-methacryloyloxyethyl phthalate and / or mono-2-(methacryloyloxy)ethyl maleate; The acryloxy acryloxy acrylate monomer is one or more of 9,9-bis[4-(2-acryloxyethoxy)phenyl], ethoxylated bisphenol A diacrylate, and 2-phenoxyethyl acrylate.
2. The chemical corrosion resistant and easy-to-clean organosilicon modified acrylic adhesive according to claim 1, characterized in that: The acryloxy acrylate monomer is composed of 9,9-bis[4-(2-acryloxyethoxy)phenyl], ethoxylated bisphenol A diacrylate, and 2-phenoxyethyl acrylate in a weight ratio of 1:(1.5-3):(2-5).
3. The chemical corrosion resistant and easy-to-clean organosilicon modified acrylic adhesive according to claim 1, characterized in that: The methacryloyloxy acrylate monomer is composed of 2-methacryloyloxyethyl phthalate and mono-2-(methacryloyloxy)ethyl maleate in a weight ratio of 1:(0.5-1.5).
4. The chemical corrosion resistant and easy-to-clean organosilicon modified acrylic adhesive according to claim 1, characterized in that: The unsaturated organic silane is methacrylate mono-terminated dimethyl polysiloxane and / or acrylic-cage polysilsesquioxane.
5. The chemical corrosion resistant and easy-to-clean organosilicon modified acrylic adhesive according to claim 4, characterized in that: The unsaturated organic silane is composed of methacrylate mono-terminated dimethyl polysiloxane and acrylic-cage polysilsesquioxane in a weight ratio of (2-3):
1.
6. The chemical corrosion resistant and easy-to-clean organosilicon modified acrylic adhesive according to claim 1, characterized in that: The nano filler is PI powder and / or silicone powder.
7. The chemical corrosion resistant and easy-to-clean organosilicon modified acrylic adhesive according to claim 6, characterized in that: The nano filler is composed of PI powder and silicone powder in a weight ratio of (2-3):
1.
8. The chemical corrosion resistant and easy-to-clean organosilicon modified acrylic adhesive according to claim 1, characterized in that: The initiator consists of a photoinitiator and a thermal initiator.
9. The chemical corrosion resistant and easy-to-clean organosilicon modified acrylic adhesive according to claim 1, characterized in that: The active diluent is epoxidized soybean oil.
10. A chemical corrosion resistant and easy-to-clean organosilicon modified acrylic adhesive according to claim 1 and a preparation method thereof, characterized in that: The following steps are involved: According to weight percentage, methacryloyloxy acrylate monomer, acryloxy acrylate monomer, unsaturated organosilane, branched hydroxy polyester, nanofiller, initiator and reactive diluent are weighed and mixed evenly to obtain an organosilicon-modified acrylic adhesive.
Citation Information
Patent Citations
Photo-setting adhesive for press key bonding injection moulding
CN101475779A
Optically-transparent dual-curing adhesive
CN102925062A
Adhesive composition
CN104271697A
Organosilicone modified acrylate high-temperature-resistant and insulating pressure-sensitive adhesive
CN110218539A
High-temperature-resistant and high-humidity-resistant photocuring adhesive and preparation method thereof
CN114621690A